Policies for small and medium-sized enterprises in Chile - Cecilia Alarcón; Giovanni Stumpo (CEPAL Review, 2001)
In 1991, the Government of Chile began to pursue a new business development strategy. The Small and Medium-sized Enterprise Support Programme (Programa de Apoyo a la Pequeña y Mediana Empresa) provides for a number of instruments to correct market failures and improve the efficiency, productivity, competitiveness and international trading position of Chilean products made by these firms. The importance of small and medium-sized enterprises (SMEs) in the national economy is illustrated by their number and by the share of jobs they create. The particularly adverse experience of the economic crises of the 1970s and 1980s, and the difficulty these companies had in adapting to the new ground rules of the open economy model, were what led the Government to decide on this new development strategy. The objective of this article is to identify and analyse the policies applied and the effects of the different actions undertaken and instruments used. Although the strategic development framework has included new instruments that have made important contributions to the SME sector, the overall impact of these is less encouraging. The challenge now facing companies of this type in Chile is to find ways of applying successful experiments on a mass scale and reformulating strategies that have not worked as well as hoped.